Personal Portable Devices in the Light of the Internet of Things - Lhotska, Lenka; Stechova, Katerina; Pharow, Peter (Studies in health technology and informatics, 2017)
Personal portable devices have already gained their position in health services. However, mobile technologies and Internet of Things open new areas of applications. The possibility to collect many data types continuously over long time intervals brings various questions that must be answered in the design process. We also discuss briefly the role of the user. We illustrate the complexity of the field by a case study of diabetes management.
Keywords: internet; zdravotnické služby; Internet; Health Services; lidé; Wearable Electronic Devices; Humans; nositelná elektronika